Cost-comparison of two trabecular micro-bypass stents versus selective laser trabeculoplasty or medications only for intraocular pressure control for patients with open-angle glaucoma. (3rd July 2017) - Berdahl, John P.; Khatana, Anup K.; Katz, L. Jay; Herndon, Leon; Layton, Andrew J.; Yu, Tiffany M.; Bauer, Matthew J.; Cantor, Louis B.
Abstract: Aim: Patients with open-angle glaucoma (OAG) whose intraocular pressure is not adequately controlled by one medication have several treatment options in the US. This analysis evaluated direct costs of unilateral eye treatment with two trabecular micro-bypass stents (two iStents) compared to selective laser trabeculoplasty (SLT) or medications only. Materials and methods: A population-based, annual state-transition, probabilistic, cost-of-care model was used to assess OAG-related costs over 5 years. Patients were modeled to initiate treatment in year zero with two iStents, SLT, or medications only. In years 1–5, patients could remain on initial treatment or move to another treatment option(s), or filtration surgery. Treatment strategy change probabilities were identified by a clinician panel. Direct costs were included for drugs, procedures, and complications. Results: The projected average cumulative cost at 5 years was lower in the two-stent treatment arm (4, 420) compared to the SLT arm (4, 730) or medications-only arm (6, 217). Initial year-zero costs were higher with two iStents (2, 810) than with SLT (842) or medications only (996). Average marginal annual costs in years 1–5 were 322 for two iStents, 777 for SLT, and 1, 044 for medications only. The cumulative cost differences between two iStents vs SLT or medications only decreased over time, with breakeven by 5 or 3 years post-initiation, respectively. By year 5, cumulative savings with two iStents over SLT or medications only was 309 or 1, 797, respectively. Limitations: This analysis relies on clinical expert panel opinion and would benefit from real-world evidence on use of multiple procedures and treatment switching after two-stent treatment, SLT, or polypharmaceutical initial approaches. Conclusions: Despite higher costs in year zero, annual costs thereafter were lowest in the two-stent treatment arm. Two-stent treatment may reduce OAG-related health resource use, leading to direct savings, especially over medications only or at longer time horizons.